TOP SOIL USAGE EFFICIENCY UP TO 73% WITH THE IMPLEMENTATION OF GROOVE SYSTEM AT LIMESTONE MINE RECLAMATION AREA PT SEMEN INDONESIA (PERSERO) TBK - Eko Purnomo; Putri Elma Octavya (Prosiding Temu Profesi Tahunan PERHAPI, 2022)
Based on Law Number 3/2020, Good Mining Practice’s criteria are mining safety provisions, environmental management, and monitoring, including reclamation and post-mining activity, conservation of minerals and coal, and management of mine waste before being released into the environment. Directorate General of Mineral and Coal state's Strategic plan reclamation target for 2021 is 7.025 hectares and 7.050 hectares in 2022. PT Semen Indonesia, as one of the mining companies, is committed to supporting the reclamation target as stated in their Yearly Land Reclamation Plan. Mine floor reclamation on limestone quarry was generally performed using top soil spreading which cost up to 3,000 m3 of top soil per hectare area. Whereas top soil availability on site is limited. As a result, the existing top soil reserve could not fulfill the needs of reclamation to cover entire mining floor. The practice of Spreading Method depletes reserved top soil, causes excessive planting media preparation and revegetation cost. This challenging condition encourages PT. Semen Indonesia to innovate to suppress reclamation cost without reducing the success rate. The company concluded that Groove Planting System could reduce both top soil transport cost and revegetation cost, even increase the survival rate of the trees. This method reduced up to 2,200 m3 of top soil usage per hectare area, reduced top soil hauling cost, reduced tree planting and treatment, even increased the success rate of reclamation. With this innovation, company could suppress reclamation cost without sacrificing reclamation quality. Benefits emerging from Groove System Implementation include; Reduced top soil volume usage for reclamation up to 73%; Reduced revegetation cost up to 49% or IDR 66,794,354/ha; Cost efficiency of planting media preparation up to IDR 168,000,000/ha; Increased tree survival rate up to 100%; Regulation mandate compliance of Post Mining Reclamation; Best practice pioneer of Post Mining Reclamation using Groove System.